The evolution of Greek Pedagogical Faculties from 1821 to today - Χατζάκης Στέργιος (Education Sciences, 2023)
The establishment and operation of primary schools in modern Greece has always been one of the first priorities of the official state, but it’s not the same situation regarding the establishment and operation of schools for the training of teachers who are to teach in primary schools. It is no exaggeration to claim that for several years after liberation, teachers had little to no formal training. This situation was improving at a very slow pace. It is only in the last half of the 20th century, with the establishment of Pedagogical Academies and even more with the establishment of Departments of Pedagogy in Universities, that we can argue that primary school teacher education has taken the place it truly deserves.